2016
DOI: 10.1371/journal.pone.0165817
|View full text |Cite
|
Sign up to set email alerts
|

Inoculated Cell Density as a Determinant Factor of the Growth Dynamics and Metastatic Efficiency of a Breast Cancer Murine Model

Abstract: 4T1 metastatic breast cancer model have been widely used to study stage IV human breast cancer. However, the frequent inoculation of a large number of cells, gives rise to fast growing tumors, as well as to a surprisingly low metastatic take rate. The present work aimed at establishing the conditions enabling high metastatic take rate of the triple-negative murine 4T1 syngeneic breast cancer model. An 87% 4T1 tumor incidence was observed when as few as 500 cancer cells were implanted. 4T1 cancer cells colonize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 65 publications
5
36
0
1
Order By: Relevance
“…However, in the group of 14 days, there were metastatic deposits in the ipsilateral SLN and contra lateral LN in 100% and 50% of animals, respectively 15 . The Study of Gregoreo and coworkers also demonstrated that inoculation of breast cancer cells 4T1 was able to induce primary tumor growth and metastasis in mice 16 . Another study reported by Neudert at al.…”
Section: Discussionmentioning
confidence: 95%
“…However, in the group of 14 days, there were metastatic deposits in the ipsilateral SLN and contra lateral LN in 100% and 50% of animals, respectively 15 . The Study of Gregoreo and coworkers also demonstrated that inoculation of breast cancer cells 4T1 was able to induce primary tumor growth and metastasis in mice 16 . Another study reported by Neudert at al.…”
Section: Discussionmentioning
confidence: 95%
“…They have been widely used as a clinically relevant triple-negative breast cancer model and are considered to represent stage IV human breast cancer. 47 Once tumors were palpable, macrophage cells were modified using the biotin/avidin-dye method to append Dy680 to the cell surface. These cells were intravenously injected into the mice ( n = 3) via tail veins.…”
Section: Resultsmentioning
confidence: 99%
“…The 4T1 triple negative breast cancer model is resistant to checkpoint blockade and this lack of response is associated with a low frequency of mutations and abundant presence of suppressive myeloid cells such as MDSCs, TAMs and TANs (Kim et al, 2014). This highly aggressive tumor model can form viable tumors when only 500 cells are implanted in mammary fat pad of female mice (Bailey-Downs et al, 2014;Gregorio et al, 2016;Pulaski and Ostrand-Rosenberg, 1998). In agreement with previous reports, 4T1 tumors were resistant to treatment with anti-PD1, anti-CTLA4, or combination of anti-PD1 and anti-CTLA4 ( Figure 1A).…”
Section: Targeting Glutamine Metabolism Inhibits Tumor Growth and Mdsmentioning
confidence: 99%